Land Cover Change in Riau Province and Its Implications for Carbon Stock and CO₂ Emissions - Ramadani Safitri; Marzuki Marzuki; Eko Priyanda; Syafira Salsabila; Ridwan Ridwan; Riki Rahman (Universitas Andalas, 2026)
This study aims to analyze peatland land cover changes in Riau Province during 2012, 2016, 2020, and 2024 and their implications for carbon stock and CO₂ emissions. The study used Landsat 7 ETM+ and Landsat 8 OLI/TIRS satellite imagery processed through supervised classification and multitemporal overlay analysis using ArcGIS. The results indicate that vegetation remained the dominant land cover class but experienced a cumulative decline of 1,393,360 ha, especially during 2016–2020 following the 2015 major fires, while built-up areas increased by 249,357 ha. This vegetation loss significantly affected carbon stocks, with an estimated loss of 418,008,000 tons C or 1,534,089,360 tons CO₂, and the 2016–2020 period contributed most to emissions. These findings confirm that peatland land cover changes are not only spatially significant but also influence carbon dynamics and greenhouse gas emissions. Multitemporal remote sensing analysis proved effective in monitoring land cover changes and estimating carbon emissions, providing a scientific basis for sustainable peatland management and regional climate change mitigation strategies.